Ethics and Corruption in the Federal Public Service : Civil Servants' Perspectives - World Bank (World Bank, Washington, DC, 2021)
This Survey on Ethics and Corruption in the Federal Public Service was held online from April 28 to May 28, 2021, in partnership with the Office of the Federal Comptroller General (CGU), the Ministry of the Economy, and the National School of Public Administration (ENAP). All civil servants were represented in the sample, totaling 22,130 respondents. The sample covered all federative units and ministries. Most civil servants report having witnessed some sort of unethical practice during their time in the public sector. Of all respondents, 58.7 percent stated that they witnessed some unethical practice during their career in public service. The most frequent practices were using one's position to help friends or family and bending the rules under pressure from one’s superiors. Over the past three years, around one third of all civil servants (33.4 percent) witnessed some unethical practice, according to their reports. Corruption in the public service is multifaceted, thus requiring granular information about its nature, prevalence, and vulnerable actors. In view of its scope, thematic scope, and representativeness, the data generated by the study could become a valuable source for the development of knowledge about corruption in the federal public service. We hope that this Survey on Ethics and Corruption in the Federal Public Service becomes a tool to complement current and future efforts to fight corruption.